"Collaborative Planning, Forecasting and Replenishment: An Introduction" - Sashikala Parimi; Mita Devi Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2006)
Collaborative Planning ; Forecasting ; Replenishment
50
Keywords: Collaborative Planning ; Forecasting ; Replenishment